Del Nido cardioplegia in adult cardiac surgery: beyond single-valve surgery. (14th February 2018) - Kim, Wan Kee; Kim, Hong Rae; Kim, Joon Bum; Jung, Sung-Ho; Choo, Suk Jung; Chung, Cheol Hyun; Lee, Jae Won
Abstract: OBJECTIVES: In recent years, the use of del Nido (DN) cardioplegia has been reported in single-valve surgery or isolated coronary artery bypass surgery with acceptable outcomes. The reports of its use in more complex adult cardiac procedures, however, have been scarce. METHODS: We enrolled a total of 149 adult patients who underwent heart valve surgery with the use of DN cardioplegia between May 2014 and December 2016. For a benchmark comparison, 892 patients who underwent cardiac valve surgery with blood cardioplegia during the same period served as controls. To reduce selection bias, propensity score matching was used; the inverse probability of treatment weighting method was performed for further validations. RESULTS: Overall, 57.7% of patients in the DN group underwent multiple or complex cardiac procedures. Early mortality rates were 0.7% and 2.4% in the DN and blood groups, respectively ( P  = 0.31). Propensity score matching yielded 111 pairs of patients who were well balanced for all 23 measured baseline covariates. In the matched cohort, the postoperative peak troponin I levels ( P  = 0.004) and the aortic clamping times ( P  < 0.001) were significantly lower and shorter compared with those in the blood group. There were no significant differences in early mortality rates (1.9% vs 0%, P  > 0.99), low cardiac output ( P  = 0.57) and neurological events ( P  = 0.21). The quantities of postoperative transfusions ( P  = 0.008) and fluid supplements ( P  < 0.001) were significantly lower in the matched DN group compared with the blood group. CONCLUSIONS: The use of DN in adult valve surgery including complex procedures may confer acceptable outcomes comparable to or even superior to those obtained with the use of blood cardioplegia.